No Path Home : Humanitarian Camps and the Grief of Displacement. - Dunn, Elizabeth C. (Cornell University Press, 2018)
"" No Path Home is an extremely interesting, engaging, and well-written book. Elizabeth Cullen Dunn's fluid and clear prose paints a very evocative picture of life for internally displaced persons as well as presenting a clear theoretical ...